(untitled) (Gilgameš, 2019)
Numerous are the comparisons that contemporary literature opens up to styles, genres and words of tradition. The dichotomy that distinguishes the choices of writing between a norm and a misrepresentation of the same has left (now perhaps more openly) the non-place of the linguistic standard emerging as a directional matrix of a more spontaneous communication, which aims to approach the competences - or presumed such - of the reader. The analysis chooses to investigate the pages of La vita prodigiosa di Isidoro Sifflotin as the winner of the Campiello Opera Prima Award in 2015; what is proposed is therefore a linguistic reasoning that can interrogate the pages of the novel to understand what expedients and narrative mechanisms have led to assign a certain literary validity to a product that, deliberately, does not choose the linguistic literary standard. .